Early role of the esc[+] gene product in the determination of segments in Drosophila. - Struhl, G.; Brower, D. (Cell, 1982)
Recent studies of the esc+ gene suggest that its product acts principally in the initiation, but not the maintenance, of segmental determination. We have tested this hypothesis by examining when the esc+ gene product is required during embryogenesis, and whether the esc+ gene product is required for the stable determination of imaginal disc cells passaged in in vivo culture. We find that the esc+ gene product is required during a discrete period of embryogenesis. If the gene product is absent or inactive during this period, most segments develop like the eighth abdominal segment. In contrast, absence of active gene product before or after this period has relatively little effect on segmental development. These results support the hypothesis that the esc+ gene product has a discrete early function in the initiation of segmental determination.